Florbetaben PET imaging to detect amyloid beta plaques in Alzheimer's disease: Phase 3 study. Issue 8 (27th March 2015) - Sabri, Osama; Sabbagh, Marwan N.; Seibyl, John; Barthel, Henryk; Akatsu, Hiroyasu; Ouchi, Yasuomi; Senda, Kohei; Murayama, Shigeo; Ishii, Kenji; Takao, Masaki; Beach, Thomas G.; Rowe, Christopher C.; et al.
Abstract: Background: Evaluation of brain β‐amyloid by positron emission tomography (PET) imaging can assist in the diagnosis of Alzheimer disease (AD) and other dementias. Methods: Open‐label, nonrandomized, multicenter, phase 3 study to validate the 18 F‐labeled β‐amyloid tracer florbetaben by comparing in vivo PET imaging with post‐mortem histopathology. Results: Brain images and tissue from 74 deceased subjects (of 216 trial participants) were analyzed. Forty‐six of 47 neuritic β‐amyloid‐positive cases were read as PET positive, and 24 of 27 neuritic β‐amyloid plaque‐negative cases were read as PET negative (sensitivity 97.9% [95% confidence interval or CI 93.8–100%], specificity 88.9% [95% CI 77.0–100%]). In a subgroup, a regional tissue‐scan matched analysis was performed. In areas known to strongly accumulate β‐amyloid plaques, sensitivity and specificity were 82% to 90%, and 86% to 95%, respectively. Conclusions: Florbetaben PET shows high sensitivity and specificity for the detection of histopathology‐confirmed neuritic β‐amyloid plaques and may thus be a valuable adjunct to clinical diagnosis, particularly for the exclusion of AD. Trial registration: ClinicalTrials.gov NCT01020838 .